Legal Certainty of Private Land Ownership Against the Control of Land by the Indonesian National Armed Forces - Gema Mutiara Insani; Muhammad Helmi Fahrozi (Dinasti Research, 2025)
The Indonesian Army’s control of the private land presents serious challenges to legal certainty in Indonesia and the protection of civilians’ rights. Disputes may arise from the Army’s physical control to the land because there is no a clear legal basis and it impacts citizens’ property rights and their economic access. This study adopts a normative juridical approach through the analysis of legal documents, laws and regulations in Indonesia, and other related academic legal literature. The inquiries shows that any control to the land without a clear legal procedure constitutes a legal uncertainty, disadvantages the land owners, and it contradicts to the rule of law and social justice. Moreover, The study also emphasizes the need for a dispute resolution mechanism through administrative and civil frameworks, alongside with the harmonization of its legal implementation, to ensure constitutional rights and mitigate future land-related conflicts between civilians and the military.